Comparative Study of γ Radiation-Induced Effects on Fiber Bragg Gratings by Femtosecond Laser Point-by-Point Method and Line-by-Line Method - Mingyang Hou; Yumin Zhang; Xin Xiong; Lianqing Zhu (Photonics)
In the realm of advanced optical fiber sensing (OFS) technologies, Fiber Bragg Grating (FBG) has garnered widespread application in the monitoring of temperature, strain, and external refractive indices, particularly within high-radiation environments such as high-energy physics laboratories, nuclear facilities, and space satellites. Notably, FBGs inscribed using femtosecond lasers are favored for their superior radiation resistance. Among various inscription techniques, the point-by-point (PbP) and line-by-line (LbL) methods are predominant; however, their comparative impacts on radiation durability have not been adequately explored. In this research, FBGs were inscribed on a single-mode fiber using both the PbP and LbL methods, and subsequently subjected to a total irradiation dose of 5.04 kGy (radiation flux of 2 rad/s) over 70 h in a 60Co-γ radiation environment. By evaluating the changes in temperature- and strain-sensing performance of the FBG pre-irradiation and post-irradiation, this study identifies a more favorable technique for writing anti-irradiation FBG sensors. Moreover, an analysis into the radiation damage mechanisms in optical fibers, alongside the principles of femtosecond laser inscription, provides insights into the enhanced radiation resistance observed in femtosecond laser-written FBGs. This study thus furnishes significant guidance for the development of highly radiation-resistant FBG sensors, serving as a critical reference in the field of high-performance optical fiber sensing technologies.